Near-petahertz fieldoscopy of liquid - Srivastava, Anchit; Herbst, Andreas; Bidhendi, Mahdi M.; Kieker, Max; Tani, Francesco; Fattahi, Hanieh (Nature Photonics, 2024)
Measuring transient optical fields is pivotal not only for understanding ultrafast phenomena but also for the quantitative detection of various molecular species in a sample. Here we demonstrate near-petahertz electric field detection of a few femtosecond pulses with 200 attosecond temporal resolution and subfemtojoule detection sensitivity. By field-resolved detection of the impulsively excited molecules in the liquid phase, termed femtosecond fieldoscopy, we demonstrate temporal isolation of the response of the target molecules from those of the environment and the excitation pulse. In a proof-of-concept analysis of aqueous and liquid samples, we demonstrate field-sensitive detection of combination bands of 4.13 μmol ethanol for the first time. This method expands the scope of aqueous sample analysis to higher detection sensitivity and dynamic range, while the simultaneous direct measurements of phase and intensity information pave the path towards high-resolution biological spectro-microscopy.
CRIS-Team Scopus Importer:2024-11-01